8y+2y+7+4x+3y=

Simple and best practice solution for 8y+2y+7+4x+3y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8y+2y+7+4x+3y= equation:


Simplifying
8y + 2y + 7 + 4x + 3y = 0

Reorder the terms:
7 + 4x + 8y + 2y + 3y = 0

Combine like terms: 8y + 2y = 10y
7 + 4x + 10y + 3y = 0

Combine like terms: 10y + 3y = 13y
7 + 4x + 13y = 0

Solving
7 + 4x + 13y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 4x + -7 + 13y = 0 + -7

Reorder the terms:
7 + -7 + 4x + 13y = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 4x + 13y = 0 + -7
4x + 13y = 0 + -7

Combine like terms: 0 + -7 = -7
4x + 13y = -7

Add '-13y' to each side of the equation.
4x + 13y + -13y = -7 + -13y

Combine like terms: 13y + -13y = 0
4x + 0 = -7 + -13y
4x = -7 + -13y

Divide each side by '4'.
x = -1.75 + -3.25y

Simplifying
x = -1.75 + -3.25y

See similar equations:

| -8-10x(-7)= | | 3x^3+9x^2+5x+15= | | 60x+20=2x+32 | | 5y+4-y-7= | | 2+5*3+4=21 | | 6x+20=2x+32 | | -(7x+1)-(-5x+9)= | | 1/6(12z-18=2z-3 | | 18*2/3-4 | | 3x(x^2-2)= | | 2/3*18-4 | | 27+4.5x= | | 5+2(x-3)=2[5-4x(x+2)] | | 9x-1(3x-1)=2 | | 5(3x+2)=8x-14-x | | 3/x(2)-5=7 | | 2x=-60 | | 32x-17x+55=100 | | logx-564=2 | | ((a^2)-(x^2))^(1/2) | | 4x(x-5)=3x+7 | | 83+-3x=55 | | 0.625*x^2-1.5*x-5=0 | | -8n-8=-72 | | f(-3)=2+2 | | 29x+7y=-17 | | 8h-5=11-14 | | 36a^2-49b^2= | | 0.9/7.2 | | 96/-5 | | -18-21x=8x-106 | | 15+0.75x=9+1.50x |

Equations solver categories